2019
DOI: 10.1016/j.aim.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Absolute continuity of harmonic measure for domains with lower regular boundaries

Abstract: We study absolute continuity of harmonic measure with respect to surface measure on domains Ω that have large complements. We show that if Γ ⊂ R d+1 is Ahlfors regular and splits R d+1 into two NTA domains, then ω Ω H d on Γ ∩ ∂Ω. This result is a natural generalisation of a result of Wu in [Wu86].We also prove that almost every point in Γ ∩ ∂Ω is a cone point if Γ is a Lipschitz graph. Combining these results and a result from [AHM 3 TV], we characterize sets of absolute continuity with finite H dmeasure both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We showed that, for such domains, ω Ω ≪ H n on the subset of any ndimensional Lipschitz graph [AAM16], and hence, for these domains, we know that absolute continuity is equivalent to rectifiability of harmonic measure (versus rectifiability of the boundary). There are fewer positive results concerning absolute continuity and rectifiability of elliptic harmonic measures.…”
Section: 3mentioning
confidence: 92%
“…We showed that, for such domains, ω Ω ≪ H n on the subset of any ndimensional Lipschitz graph [AAM16], and hence, for these domains, we know that absolute continuity is equivalent to rectifiability of harmonic measure (versus rectifiability of the boundary). There are fewer positive results concerning absolute continuity and rectifiability of elliptic harmonic measures.…”
Section: 3mentioning
confidence: 92%
“…Beyond that, in a Wiener regular domain with large complement (cf. [1, Definition 1.5]), Akman et al [1] gave a characterization of sets of absolute continuity in terms of the cone point condition and the rectifiable structure of elliptic measure. Let us point out that in all of the just mentioned results, the absolute continuity happens locally.…”
Section: (B)mentioning
confidence: 99%
“…x ∈ ∂ for every weak solution u ∈ W 1,2 loc ( ) ∩ L ∞ ( ) of Lu = 0 in and for all (or for some) r > 0. (e) For every weak solution u ∈ W 1,2 loc ( ) ∩ L ∞ ( ) of Lu = 0 in and for σa.e. x ∈ ∂ there exists r x > 0 such that S r x α u(x) < ∞.…”
Section: (B)mentioning
confidence: 99%
“…If H d | ∂Ω were σ-finite, then it would have tangents on a set K ⊆ ∂Ω of positive H d -measure by Theorem I . Theorem III in [AAM16] says that H d ω H d on the set of interior cone points for Ω, and since tangent points are also cone points, it follows from that H d ω H d on K. Since dim ω < d, we can find E so that H d (E) = 0 and ω(E ∩ K) = ω(K) > 0, but the mutual absolute continuity would imply 0 = H d (E) ≥ H d (E ∩ K) > 0, a contradiction, and thus proves the corollary.…”
Section: Introductionmentioning
confidence: 99%